Social Status of Researchers And Professional Practices in the Field of Research Aimed at Social Intervention in France - Tremblay, Marc-Adélard (Culture, 1990)
During a governmental mission to France in March of 1988 the author evaluated the effects of the status and professional practices of researchers on their work in the field of ‘social research’. This type of research is largely financed by sectorial ministeries and private associations formed under the provisions of the law of 1901. I examined the sociopolitical and scientific milieu of knowledge production in this field of study. Such research on social aspects of health, social problems and income security raises fundemental epistemological questions regarding its legitimacy, specificity, scientific validity, and applicability. A traditional theoretical orientation in social science research, lack of interest in funding this type of research at the CNRS (Centre National de la Recherche scientifique) and scientific ministries, and the precarious status of young researchers all characterize this new field of study and also constrain its development. However a new momentum is under way, due to recent initiatives by the Mission de Recherche et d’Experimentation (MIRE), the Ministère des affaires sociales et de l’emploi, and to political lobbying by public bodies and private organizations with the goal of revitalizing social research aimed at finding concrete and innovative solutions to contemporary problems through the application of research.